Evaluation and phytochemical screening and antibacterial activity of Ficus dalhousiae Miq (International Journal of Research In Phytochemical And Pharmacological Sciences, 2019)
The aim of the present study was to isolate the Extract from the leaves of Ficus dalhousiae Miq and subse-quently evaluate their antibacterial and antifungal activity. The crude various extracts of the plant n-Hexane, Chloroform, Ethyl acetate, Methanol extract was obtained by using continuous soxhlation tech-nique using soxhlet apparatus. The antibacterial activity of plant extract were carried using cup plate method against three bacterial species Staphylococcus aures, Bacillus subtilis, Escherichia coli using agar diffusion method. those are compared with standard reference drug Ciprofloxacin. This study confirmed that bark extracts have more active constituents compare to leaf extracts. by pharmacological evaluation of Ficus dalhousea Miq. Various extracts, most of them are capable of showing moderate antibacterial activity.